Delineating gene–environment effects using virtual twins of patients treated with clozapine. (24th November 2022) - Mostafa, Sam; Polasek, Thomas M.; Bousman, Chad; Rostami‐Hodjegan, Amin; Sheffield, Leslie J.; Everall, Ian; Pantelis, Christos; Kirkpatrick, Carl M. J.
Abstract: Studies that focus on individual covariates, while ignoring their interactions, may not be adequate for model‐informed precision dosing (MIPD) in any given patient. Genetic variations that influence protein synthesis should be studied in conjunction with environmental covariates, such as cigarette smoking. The aim of this study was to build virtual twins (VTs) of real patients receiving clozapine with interacting covariates related to genetics and environment and to delineate the impact of interacting covariates on predicted clozapine plasma concentrations. Clozapine‐treated patients with schizophrenia ( N = 42) with observed clozapine plasma concentrations, demographic, environmental, and genotype data were used to construct VTs in Simcyp. The effect of increased covariate virtualization was assessed by performing simulations under three conditions: "low" (demographic), "medium" (demographic and environmental interaction), and "high" (demographic and environmental/genotype interaction) covariate virtualization. Increasing covariate virtualization with interaction improved the coefficient of variation ( R 2 ) from 0.07 in the low model to 0.391 and 0.368 in the medium and high models, respectively. Whereas R 2 was similar between the medium and high models, the high covariate virtualization model had improved accuracy, with systematic bias of predicted clozapine plasma concentration improving from −138.48 ng/ml to −74.65 ng/ml. A high level of covariate virtualization (demographic, environmental, and genotype) may be required for MIPD using VTs.